Dental health among older Israeli adults: is this a reflection of a medical care model inadequately addressing oral health? - Sgan-Cohen, Harold; Livny, Alon; Listl, Stefan (International dental journal, 2015)
Objectives Israel's health-care system is considered as one of the most efficient worldwide. The purpose of the present study was to assess oral health outcomes, dental care use and respective social inequalities among the older segment of the Israeli population. Methods Secondary analyses were conducted of recently available data from the Survey of Health, Ageing, and Retirement in Europe (SHARE Israel, wave 2), which specifically includes information on chewing ability, denture wearing and dental care use obtained from more than 2,400 Israeli people, 50+ years of age. Multivariate logistic regressions and concentration indices were used to analyse determinants of oral health and dental care use. Results Seventy per cent of respondents reported being able to bite/chew on hard foods and 49% of respondents reported wearing dentures. Forty-three per cent of respondents had visited a dentist within the past 12 months, with about half of all dental visits being made for solely nonpreventive reasons. Significant income-related inequalities were identified, with higher income being associated with greater dental care use (particularly preventive dental visits), better chewing ability and less denture wearing. Conclusions For the older segment of the Israeli population and compared with other countries, the findings of the present study suggest a relatively low level of chewing ability, a high extent of nonpreventive dental visiting, as well as considerable inequalities in oral health and care. It seems that the Israeli health-care system may be improved even further by more comprehensive inclusion of dental care into universal health coverage.
First published: 24 October 2014
Gesehen am 17.06.2020